PERLINDUNGAN TERHADAP ANAK-ANAK KORBAN BENCANA DITINJAU DARI KONVENSI HAK-HAK ANAK DAN HUKUM NASIONAL - Ria Tresnomurti (LPPM STIH Awang Long, 2023)
In every disaster, children are the most vulnerable group to become victims and suffer. son has not been able to save himself, so the chances of becoming a victim are greater. As a result, they experience physical and psychological trauma. The risks to children are enormous, coupled with the nature of disasters that can come at any time, forcing them to receive special protection, in accordance with the mandate of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. The government, regional governments and other state institutions are obliged to provide special protection to children in emergency situations, including children who are victims of natural disasters. In this paper the author uses a normative juridical approach, because of this approach, this model of legal research is called normative legal research. Legal provisions are the primary legal material for Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection.